If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11-x=75-(-1x)
We move all terms to the left:
11-x-(75-(-1x))=0
We add all the numbers together, and all the variables
-1x-(75-(-1x))+11=0
We calculate terms in parentheses: -(75-(-1x)), so:We get rid of parentheses
75-(-1x)
determiningTheFunctionDomain -(-1x)+75
We get rid of parentheses
1x+75
We add all the numbers together, and all the variables
x+75
Back to the equation:
-(x+75)
-1x-x-75+11=0
We add all the numbers together, and all the variables
-2x-64=0
We move all terms containing x to the left, all other terms to the right
-2x=64
x=64/-2
x=-32
| -6y+3(y+3)=18 | | 0.7x8.4= | | x/60=5 | | -15x+4=-14x+11 | | 12-9/16x=6 | | 124+81+90+x=360 | | 2m+113=9 | | 6+-20+y/3=1 | | 50+28+x=180 | | 3x+4-10x-1=31 | | 3/5x=49 | | 6x^2+5=20 | | 6+4k=-5+15 | | 3x+15+75=90 | | 6x2+5=20, | | 10.50=x+1.50 | | 3x+15-75=180 | | 3x-15+75=90 | | 40-15x=20 | | h-9=11 | | 3x-15-75=180 | | 3-2(3x-5)=-3x+1+15 | | r-5=15 | | 3n-18=9 | | 3x-9=5x-4+21-3 | | 6x+6=26x-91 | | -3.1x+7-7.4x=1.5x-6(x-32) | | 25+x-10=20 | | 7-3+12=x+6 | | 0/3r=2/1 | | –19t−–7t−6t+20t−–11=–15 | | 7x+12x=93 |